Self-care practice, lived experience of type 1 diabetes mellitus patients at Kemisse General Hospital, North Eastern Ethiopia: Phenomenological study - Eyob Ketema Bogale; Habtamu Wondiye; Yamrot Debela; Tadele Fentabil Anagaw; Lelisa Worku; Natnael Kebede (SAGE Open Medicine, 2022)
Objectives: To explore self-care experience of type 1 diabetes mellitus patients at Kemisse General Hospital, North east Ethiopia. Methods: A phenomenological study was conducted to explore self-care experience of type 1 diabetes mellitus patients at Kemisse General Hospital from 28 February 2020 to 15 March 2020. Participants were selected using a heterogeneous type of purposive sampling technique. Data were collected using in-depth interviews and observation with the aid of an audio recorder and interview guide by the principal investigator. The thematic analysis approach was used to analyze the data. To facilitate the data analysis process, Atlas. ti software version 7 was used. Results: The six interconnected themes that were emerged from the analysis are: (1) physical exercise, (2) dietary practice, (3) medication adherence, (4) self-monitoring of blood sugar, (5) problem-solving skill during hypoglycemia and hyperglycemia, and (6) diabetic foot care. Conclusion: The study described that type 1 diabetic patients at Kemisse general hospital faced difficulty in self-care practice, which were difficulty in medication adherence; foot care was neglected diabetes self-care, did not practice diabetes recommended dietary plan and lack of regular physical exercises. In addition to this, self-monitoring of blood sugar was not practiced regularly due to the absence of glucometer machine and financial constraints to buy test strips. In addition to diabetic patient’s role to manage hyperglycemia and hypoglycemic episode, family support was crucial to managing hypoglycemia because most of the respondent’s experience loss of consciousness during a hypoglycemic attack.